PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP NEGERI 1 KUOK - Fitria Hidayat; Zulhendri Zulhendri; Zulfah Zulfah (Departement of Mathematics Education, 2018)
This study aims to determine whethe there is the influence of type TPS kooperatif learning model of mathematical problem solving ability junior high student in grade VII Negeri 1Kuok. This study is experimental study. Sampling technique using sampling techniques random. The subject of this study were grade students as aclass experiment VII D and grade students as a control class.Data collection techniques by doing dokumentasi, observation and test. In this study, meetings were held for five times, four meetings with implementing type models of cooperative learning TPS and one more meeting held posstest. To find out the result of the study investigatigators to manually calculate your own data. Based on the results obtained by use within the data, analyzed using the test “t” . analysis of data showed the value tcount = 8,79 and t table significant level of 5% and 1% at 2,01 and 2,68. This shows that (2,01<8,79>2,68), which means H0 rejected andHa accepted. Thus, itcan be concluded that there are type effect of cooperative learning model of problem solving TPS againt the students math class VII SMP Negeri 1 Kuok.